Ketentuan Perjanjian Kerja Tertentu - Budiyanto, Achmad Farid; Huda, Miftakhul (Jurnal Ilmu Sosial dan Humaniora, 2026)
A Fixed-Term Employment Agreement (PKWT) is an employment relationship instrument regulated by Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning Job Creation and Government Regulation Number 35 of 2021. PKWT is intended for temporary or fixed-term work to create flexibility in employment relationships and legal certainty. However, in practice, the implementation of PKWT shows significant differences between Regionally-Owned Enterprises (BUMD) and private companies. BUMDs have dual functional characteristics, namely profit orientation and public service, so that the implementation of PKWT is influenced by internal regulations and regional government supervision. Meanwhile, private companies implement PKWT with a higher degree of flexibility, but it has the potential to lead to abuse of workers' rights. This study uses a normative legal research method with a statutory approach to examine the regulation and implementation of PKWT in both entities. The results show that although PKWT falls under the same labor law regime, differences in business entity characteristics affect implementation, legal certainty, and labor protection